Analisis Hubungan antara KAP (Knowledge, Attitude, and Practice) Peternak Sapi terhadap Penggunaan Antibiotik di Kecamatan Alak, Kecamatan Maulafa, dan Kecamatan Kelapa Lima, Kota Kupang - Moscatia Tobilolon Muda; Novalino H. G. Kallau; Annytha I. R Detha (Jurnal Veteriner Nusantara, 2022)
Antibiotics are one type of antimicrobial that is often used by farmers because of several benefits as therapeutic agents, prophylactic agents, to as feed additives to support livestock growth, especially with meat products (Antibiotic Growth Promoters or AGP). The study was to find out how knowledges and attitudes towards antibiotics affect the practice of using antibiotics by farmer, conducted on cattle farmers in 3 sub-districts in Kupang City, namely Alak, Maulafa, and Kelapa Lima sub-districts. The sampling technique was carried out using a purposive technique where the samples taken had certain criteria namely had been raising cattle for more than 1 year. Sampling was done by knowing in advance the population of the Head of Family (KK) from the three sub-districts, namely as many as 14,924 families, then using an error of 10% obtained a sample of 99 families as respondents.Data analysis was carried out using Pearson correlation to see the relationship between knowledge and attitudes towards the practice of using antibiotics, it was found that there was a significant relationship between knowledge towards attitudes and practice at P < 0.01, and attitudes towards practice at P < 0.01. While the results of the path analysis show that there is an indirect relationship between knowledge and practice through attitudes of 0.388, and a direct relationship between attitudes towards practice of 0.690.